Physical Therapy Management in Femoral Ollier Disease - Ida Ayu Made Pradnyanini; I Putu Gde Surya Adhitya (Physical Therapy Journal of Indonesia, 2020)
Introduction: Ollier disease (OD) is a non-hereditary, an uncommon bone disorder that typically presented by multiple or unilateral enchondromatosis associated with the deformity of the extremities. This article describes a case of a patient with OD that contribute endochondral ossification of the femoral bone and the physical therapy management.Case Description: An eight years old female patient referred to physical therapy unit after resection of right femur enchondroma, had undergone surgery for bone lengthening with external fixation. Further, the patient has been undergone surgical intervention for the tibial enchondromatosis. Physical therapy management aimed to improve the range of motion, pain, gait pattern, and activity of daily living. After three sessions of intervention, the patient reported the improvement in the pain and range of motion of the right lower limb.Conclusion: The physical therapy management might improve the pain and lower limb range of motion after the surgical intervention in femoral OD.